Evaluation of the potential of Melastoma malabathricum L. and Ricinus communis L. for heavy metals phytoremediation on soil contaminated with sewage sludge - Patek Mohd, Nur Hazirah (2016)
The increasing human population every year has resulted in an enormous volume of sewage sludge throughout the world. Disposing of sewage sludge is a major concern due to its high concentrations of heavy metals. These heavy metals need to be removed before they are applied on soils as an amendment. Phytoremediation is a biological treatment by which plants are used to remove pollutants from the soil environment. The objectives of this study were to evaluate heavy metals uptake and translocation in plant parts; to quantify the heavy metals concentrations of sewage sludge in the growth medium before the planting and after the harvesting period; and to quantify the percentage of reduction of heavy metals from the initial metals input and leaching studies. Seedlings were planted on six different growth media – a control (100% soil), T1 (80% soil + 20% sewage sludge), T2 (60% soil and 40% sewage sludge), T3 (40% soil + 60% sewage sludge), T4 (20% soil + 80% sewage sludge) and T5 (100% sludge) for 6 months. In this study, a Randomized Complete Block Design (RCBD) was used. Plant heights and number of leaves were measured every month during the study period. Plant biomass was measured using plant parts (leaves, stems and roots) and total concentrations of heavy metals were determined by Atomic absorption spectrophotometry (AAS). For Melastoma malabathricum, the best plant height was in T2 (40% sewage sludge + 60% soil), with a value of 104 cm, and the highest number of leaves was in T3 (60% sewage sludge + 40% soil), with a value 975. The best growth performance for Ricinus communis was 114 cm in T1 (100% soil) for plant height, and 11 in T1 (100% soil), for number of leaves. In these experiments, both species were able to reduce heavy metals in the soil.The highest concentration of Cu after harvest was detected in T5 (4.93 mg/kg) for Ricinus communis. The highest total Cu concentration in plant parts, with value of 0.45 mg/kg, was treatment T0 for Melastoma malabathricum. The highest Fe concentration in growth media after the harvest was 1602.13 mg/kg in T5 (Ricinus communis), while all species stored the highest Fe concentrations in T5. Ricinus communis was not suitable as an accumulator plant for Fe because its BF and TF values were below 1 in T5 (9.73 mg/kg). Both species can be considered accumulators of Mn due to their high TF values, and both were able to translocate and accumulate Mn from their roots to their shoots after taking it from the soil. The highest total Pb concentration was in T5, with a value of 10.35 mg/kg, for Melastoma malabathricum and Ricinus communis, which both can be considered accumulators of Pb, having BF and TF values above 1. The highest concentration of Zn in the growth medium was in T5, with a value of 47.75 mg/kg, for Melastoma malabathricum. With TF values of more than 1, both species were suitable as accumulators of Zn. There is lack information about removal heavy metals from soil contaminated with sewage sludge through leaching during phytoremediation process. The results demonstrate Fe concentrations in leachate was highest compared to Cu, Mn, Pb and Zn. The highest leachate was Fe with value 74.56 mg/L in T0 and Ricinus communis leached out more Fe elements compared Melastoma malabahtricum. The highest percentage reduction of heavy metals was recorded for Melastoma malabathricum in T2 (Cu), with values of 53.17%, while the highest for Ricinus communis was ecorded in T1 (Zn), with values of 54.89%. This research found that Melastoma malabathricum and Ricinus communis can be used as phytoremediators of Cu, Mn, Pb and Zn due to their ability to accumulate the elements in the roots and translocate them to the shoots. None of the species were capable of being accumulators of Fe because their BF and TF values were lower than 1.